TRADISI MUJAHADAH HASYRAN DI PONDOK PESANTREN SUNAN PANDANARAN YOGYAKARTA: STUDI LIVING HADIS - Nizam Zulfa; Anis Fajar Fitria; Tafsirotu Rohmah (An-natiq Jurnal Kajian Islam Interdisipliner, 2021)
Mujahadah phenomen in each pondok pesantren nowadays has already become a trend in pesanten  society. As a tradition in one of pesantren at Ngaglik Sub-district Sleman Regency is that Mujahadah Hasyran tradition is relate with Merapi Mountain eruption which had happened approximately in the middle of  2010’s end. And than this Mujahadah continuously exist until now after doing Maghrib prayer and became a compulsory habit in Pondok Pesantren Sunan Pandanaran. The main of this event is recitating Surah al-Hasyr. Mujahadah Hasyran is also involved Hadits Text. The existence of Hadist is also called important, because hadist's role is for explaining some cases in Qur'an.  The aim of Mujahadah is for security and make a peace soul for the victims. In this research of hadist, researchist used social construction theory which written by Peter L. Berger. Research’s theory is a construction in Mujahadah Hasyran comprehension in dialect concept contained in three steps, they are externalization, objectification, and internalization. According to the result of research, it can be implied that tradition isn't come without a cause, meanwhile it's for security that has been noted above.  Based on study living hadis, this tradition relates with Imam Tirmidzi in his Sunan book.